Kepemimpinan Klinis terhadap Kualitas Pelayanan Keperawatan - Elfina Elfina; Bustami Syam; Siti Zahara Nasution (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the effect of clinical leadership (quality of self, collaboration, managing services, improving service quality and setting goals) on the quality of nursing services at the University Hospital of North Sumatra. The method used is a cross-sectional survey of 94 respondents. The results showed that the p-value for the self-quality variable was 0.000, clinical leadership was 0.001 and the variable improved service quality was 0.004 for the quality of nursing services. In conclusion, there is an effect of self-quality, clinical leadership, managing services, improving service quality and setting goals on the quality of nursing services at the University Hospital of North Sumatra. Self-quality is the most influential variable in the quality of nursing services at the University Hospital of North Sumatra. Keywords: Clinical Leadership, Nursing, Quality of Service